2021
DOI: 10.1186/s12872-021-01998-4
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0004831 downregulation is partially responsible for atorvastatinalleviated human umbilical vein endothelial cell injuries induced by ox-LDL through targeting the miR-182-5p/CXCL12 axis

Abstract: Background The dysfunction and injury of human umbilical vein endothelial cells (HUVECs) are key events of atherosclerosis (AS). Atorvastatin (ATV) has been shown to play a protective role on endothelial cells. However, the associated molecular mechanisms remain not fully illustrated. Methods HUVECs were treated with oxidized low-density lipoprotein (ox-LDL) to mimic the pathological conditions of endothelial cell injury in AS. Cell injuries were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…28 Meanwhile, miR-182-5p restoration could partly eradicate the effects of hsa_circ_0004831-induced injuries of human umbilical vein endothelial cells. 29 Previously, the rats suffering from myocardial infarction have been shown to exhibit increased inflammatory factors, blood lipid indexes, TGF-β mRNA and protein expression, and Smad2 phosphorylation, whereas after the TGF-β/Smad pathway blockage, the rats showed notably opposite trend. 30 The interaction between HDAC1 and the TGF-β/Smad pathway has been implicated in renal interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…28 Meanwhile, miR-182-5p restoration could partly eradicate the effects of hsa_circ_0004831-induced injuries of human umbilical vein endothelial cells. 29 Previously, the rats suffering from myocardial infarction have been shown to exhibit increased inflammatory factors, blood lipid indexes, TGF-β mRNA and protein expression, and Smad2 phosphorylation, whereas after the TGF-β/Smad pathway blockage, the rats showed notably opposite trend. 30 The interaction between HDAC1 and the TGF-β/Smad pathway has been implicated in renal interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-182 has been demonstrated that promote epithelial-mesenchymal transition, invasion and migration and angiogenesis in both breast cancer [39] and HCC [40]. Meanwhile, miR-182-5p could promote the proliferation, migration and angiogenesis of HUVECs [41], indicating the potential role of anti-angiogenic effect in endothelial cells of diabetes. In the current study, we demonstrated that miR-182-5p can positively regulate the diabetic wound healing by targeting PPARG.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell apoptosis is the main form of endothelial injury and plays an important role in the occurrence and development of AS [ 21 ]. Ox-LDL can lead to endothelial cell injury and promote the occurrence and development of AS [ 22 ]. The results also identified this phenomenon, that is, 50 µg/ml ox-LDL caused the decreased viability of HUVECs.…”
Section: Discussionmentioning
confidence: 99%